Suicide Prevention Programs Led by Nurses: A Scoping Review of Approaches and Effectiveness - Wahyu Dini Candra Susila; Salwa Nirwanawati; Fitrio Deviantony; Enggal Hadi Kurniyawan; Robby Prihadi Aulia Erlando; Caturia Sasti Sulistyana (Journal of Health, Sport, and Nursing, 2025)
Background: Suicide remains a major global cause of death, with nurses positioned as key providers for early detection, risk management, and follow up of individuals at risk. Nurse led programs are increasingly implemented, yet their approaches and effectiveness are dispersed across settings and study designs. Aim: To map approaches and effectiveness of nurse led suicide prevention programs and identify gaps for practice and policy. Setting: Hospitals, emergency departments, nursing homes, community and educational services, and organizational settings involving nurses and nurse leaders. Methods: A scoping review was conducted using PubMed, Scopus, Web of Science, and CINAHL, complemented by manual searching. Included were primary English language studies (last 5 years) on nurse led suicide prevention interventions reporting clinical or educational outcomes. Study selection followed PRISMA ScR; data were extracted on intervention characteristics and outcomes, and synthesized narratively. Results: Ten studies were included, grouped into nurse led safety planning, brief gatekeeper training, vocational/academic curricula, and organizational interventions. Across studies, programs improved suicide related knowledge, self efficacy, skills, and willingness to intervene among nurses, nursing students, and allied gatekeepers, while a few suggested potential effects on suicidal behavior. However, most used pre post designs without controls, small samples, and short follow up. Conclusion: Nurse led suicide prevention programs enhance competencies and organizational readiness to respond to suicide risk, but stronger evidence is needed for long term clinical impact.